Surface modification of nanosilica from sugarcane bagasse waste ash using methyltrichlorosilane (MTCS), triethoxymethylsilane (TEMS) and triethoxyvinylsilane (TEVS) to produce a hydrophobic surface on glass substrate - Chareon Panyo (2020)
© 2020, Chiang Mai University. All rights reserved. Bagasse ash is a biomass source and a valuable byproduct of sugar milling, which often uses bagasse as a primary fuel source to supply energy to move the plants. Burning bagasse as an energy source yields ash, considered to be a waste product, causing disposal problems. However, sugarcane bagasse ash from the sugar industry is a source of silica. A simple method based on alkaline extraction followed by acid precipitation can be used for its extraction. The purpose of this work was to modify the hydrophobic surface of nanosilica obtained from sugarcane bagasse ash using commercial silanes as coupling agents and coat a glass substrate. Superhydrophobic films with silane-modified silica nanoparticles were successfully prepared. Silica nanoparticles from sugarcane bagasse ash were modified by organosilanes using methyltrichlorosilane (MTCS), triethoxymethylsilane (TEMS), and triethoxyvinylsilane (TEVS) as modifying agents. Desired surface chemistry and texture growth for superhydrophobicity developed under spray coating process at room temperature. The coated surfaces were characterized by Field-emission scanning electron microscopy (FE-SEM) and measurement of water contact angle (WCA). WCA of coated glass surface increased with increased nanosilica content. The optimal conditions produced a contact angle of 151.76° and yielded superhydrophobicity; these were 5 %wt nanosilica in a mixture of methyltrichlorosilane in toluene at a volume ratio of 0.15. This method could be effective for fabricating self-cleaning superhydrophobic surfaces and has promising applications.